Diversity attitudes and sensitivity of employees and leaders in the German STEM-sector - Genkova, Petia; Schreiber, Henrik (Frontiers in Psychology, 2022)
The increasing diversity of cultural backgrounds, migration status and age is shaping modern working life. Previous research demonstrated that the attitudes and competences of team members and leaders towards diversity play a crucial role in utilizing the potential of heterogenous teams and preventing detrimental behavior and discrimination. But even though leaders appear to be key figures in the process of diversity management, their perception of diversity as well as related challenges and chances are poorly investigated. The current paper aims to contribute to the understanding of leaders’ perspective on and role in diversity management building on a comparative analysis of two explorative qualitative studies with sixteen employees and twenty-two leaders. The overall research questions are how employees and leaders perceive diversity of culture and age from their specific point of view, which experiences are likely to contribute to their opinion on and perception of diversity and in how far do employees and leaders differ in these aspects. Participants come from the German sector of science, technology, engineering and mathematics (STEM), which is the most internationalized and least psychologically investigated sector in Germany. The results show that employees are aware of the topic of diversity in general but have poor competences in dealing with diversity in their daily working life. This seems to be associated with lack of experience with intercultural interaction and a lack of support from the respective organizations/leaders. We further found that individuals with a migration background do not show any signs of stereotype threat rather than expressing a feeling of being isolated from employees without a migration background. By Comparing perspectives of leaders and employees, the current study contributes to the understanding of the processes that underly experiences of inequalities of migrants and experiences of intercultural miscommunication and faultlines of people without migration background. Theoretical and practical implications are discussed.